Peran Orang Tua di Rumah dalam Mengembangkan Disiplin Anak di Lingkungan Masyarakat - Wulandari, Hayani; Nurfalah, Fani (Peneliti.net, 2024)
This study aims to comprehensively explore the role played by parents in the home environment in shaping children's discipline in the context of society. Applying quantitative research methods, this approach utilized questionnaires as data collection instruments administered to parents. The study specifically explored parents' perceptions regarding key aspects of child discipline, including but not limited to, rule formation, application of punishment, rewarding, and consistency in their approach to discipline. The data analysis provided in-depth insights, providing a clearer understanding of the discipline strategies that proved effective and the concrete contributions made by parents in shaping children's disciplinary behavior. The results of this study not only provide a better understanding of the dynamics of the role of parents in this context but also offer a significant contribution to the literature relating to the development of child discipline in community settings. The findings of this study, thus, have potentially great relevance and implications in the context of child education and development.